DNA barcoding reveals the temporal community composition of drifting fish eggs in the lower Hongshui River, China - Weitao Chen; Shuli Zhu; Jiping Yang; Xinhui Li; Yuefei Li; Jie Li (Ecology and Evolution, 2021)
Abstract Determining the temporal community composition of fish eggs in particular regions and understanding the reproductive times of regional fish taxa are key aspects of the management and regulation of regional fish stocks. However, it is extremely difficult to accurately identify fish eggs due to the absence of diagnostic morphological characters. We sampled fish eggs in the lower Hongshuihe River (an upper mainstem of the Pearl River) between May and September 2020. We then used DNA barcoding to determine the species composition of the egg pool and to predict the spawning periods of the identified species. A total of 641 eggs and 17 larvae were chosen for molecular identification; 397 eggs and 17 larvae yielded high‐quality barcoding sequences. The high failure rate (~38%) was most likely due to long‐term storage in low concentrations of ethanol prior to molecular analysis. We successfully classified 392 eggs into 10 species and 13 larvae into four species using public databases. Most of the species identified in the egg pool were small and/or benthic, and migratory species were rare. This may partially reflect the adverse effects of hydropower cascade development in this river section. We also found that spawning periods tended to be species‐specific. Our study provides a reference for the conservation and management of regional fishery stocks.